Analisis Hubungan Tingkat Pengetahuan terhadap Perilaku Swamedikasi Batuk selama Masa Pandemi Covid-19 - Lusi Ariska Triani; Hariyanto IH; Shoma Rizkifani (Journal Syifa Sciences and Clinical Research, 2022)
The Covid-19 pandemic gave an impact on the limitation of health services in health facilities, causing people to choose self-medication as their treatment method. The purpose of this study is to determine the level of knowledge and self-medication behavior of cough symptoms in Rasau Jaya District and the correlation between those two variables during the Covid-19 pandemic. Cross-sectional design with purposive sampling technique was used as a research method for 75 respondents and questionnaires were used as a measuring tool. Data processing was carried out using SPSS statistical tests. We found that none of the respondents had low knowledge levels with 71 respondents (94,7%) having a good level of knowledge and 4 respondents (5,3%) having sufficient levels. This result are in line with self-medication behavior showed that 73 respondents (97,3%) have a good level of behavior at doing self-medication of cough and 2 respondents (2,7%) have deficient levels. The majority people in Rasau Jaya District have a good level of knowledge and self-medication behavior and we found that there is a correlation between those two variables.